Intersectionality of gender, race/skin color and dental loss in adults: cross-sectional study with data from the 2019 Brazilian National Health Survey - Bianca de Oliveira Farias; Larissa Fortunato Araújo; Nayranne Hivina Carvalho Tavares; Bárbara Bruna Rodrigues de Oliveira; Mayra Solange Lopes de Vasconcelos; Soraia Pinheiro Machado (Epidemiologia e Serviços de Saúde, 2025)
Abstract Objective To evaluate the association between intersectionality of gender, race/skin color and dental loss of 13 or more teeth among Brazilian adults. Methods Cross-sectional study using data from the 2019 Brazilian National Health Survey. The response variable was dental loss of 13 or more teeth, the exposure was the intersectionality of gender, race/skin color, and the association was analyzed using logistic regression. Odds ratio (OR) and 95% confidence intervals (95%CI) were calculated. Sequential adjustments were made for age, education and macroregion of Brazil. Results Among the 73,813 adults, higher odds of dental loss were observed in white women (OR 1.38 [95%CI 1.21; 1.56]) and Black women (OR 1.70 [95%CI 1.53; 1.89]) compared to white men, even after full adjustment. Among Black men, no significant differences were observed compared to white men regarding dental loss. Conclusion Dental loss is associated with the intersectionality of gender, race/skin color. White and Black women appear to be more susceptible to dental loss. Social mechanisms such as racism and sexism may be intrinsically linked to the observed patterns of dental loss, highlighting the need to include actions on these mechanisms in existing national oral health policies, prioritizing disadvantaged segments.